2015
DOI: 10.1016/j.parkreldis.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic denervation severity depends on COMT Val158Met polymorphism in Parkinson's disease

Abstract: Striatal denervation differs according to COMT-Val158Met polymorphism. COMT activity may play a role as a compensatory mechanism in PD motor symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
2
9
0
1
Order By: Relevance
“…We also found increased levels of caudate DAT in Met/Met carriers of COMT polymorphism. This is consistent with a 18 F-DOPA PET study, which found higher presynaptic dopamine levels in frontal regions in Met/Met [26], and in controversy with a recent study that found higher levels of striatal FP-CIT BP in Val/Val [27]. However, this last result could be a false positive due to a small sample size (40 subjects in total, and only 3 Met/Met carriers).…”
Section: Discussionsupporting
confidence: 90%
“…We also found increased levels of caudate DAT in Met/Met carriers of COMT polymorphism. This is consistent with a 18 F-DOPA PET study, which found higher presynaptic dopamine levels in frontal regions in Met/Met [26], and in controversy with a recent study that found higher levels of striatal FP-CIT BP in Val/Val [27]. However, this last result could be a false positive due to a small sample size (40 subjects in total, and only 3 Met/Met carriers).…”
Section: Discussionsupporting
confidence: 90%
“…11 The A allele was associated with a reduction of 3-to 4-fold in the enzyme activity, being designated as L (low activity), whereas the G allele has been called H because it is associated with higher enzymatic activity. 12 In addition, the MAO-B gene contains a single-stranded conformational polymorphism within intron 13 (rs1799836), which results in a transitional conversion of adenine (A) to guanine (G) creating a splicing enhancer, thus changing the enzymatic activity. [13][14][15] The impact of genetic variants in the choice of the more adequate PD treatment is still controversial.…”
mentioning
confidence: 99%
“…The nonsynonym SNP rs4680 in COMT , a G→A transition (valine‐methionine substitution) on codon 158 (exon 4) of the membrane‐bound transcript variant, has been associated with the modulation of enzyme activity . The A allele was associated with a reduction of 3‐ to 4‐fold in the enzyme activity, being designated as L (low activity), whereas the G allele has been called H because it is associated with higher enzymatic activity . In addition, the MAO‐B gene contains a single‐stranded conformational polymorphism within intron 13 (rs1799836), which results in a transitional conversion of adenine (A) to guanine (G) creating a splicing enhancer, thus changing the enzymatic activity …”
mentioning
confidence: 99%
“…Кодирующий метионин аллель А связан со снижением ферментативной активности в 3-4 раза и, как следствие, обусловливает высокое содержание леводопы и дофамина. Кодирующий валин аллель G, напротив, ассоциирован с более высокой активностью фермента, что приводит к быстрому снижению концентрации дофамина в синаптической щели [11]. M. Bialecka и соавт.…”
Section: о б з о р ыunclassified